Quality of Work-Life and Work-Life Balance as Predictors of Employee Job Satisfaction - Abiodun Adekunle Ogunola (‎‎‎TAZKIYA Journal of Psychology, 2022)
Finding the right balance between one's work and other facets of life is essential for an individual to be in the right state of mind and to be satisfied with one's job that one commits to. Specifically, it aims to determine whether the quality of work-life and work-life balance would predict employees' job satisfaction in the selected banks. A survey research design consisting of 100 workers was selected from branches of selected banks in Ijebu-Ode, Ogun State, Nigeria, wherein they responded to questions relating to the variables of interest in the study. The result of the study revealed that quality of work-life and work-life balance has a significant influence on job satisfaction (β= .648, t= 8.597, p> .05) and work-life balance also has a significant influence on job satisfaction (β= .212, t= 2.849, p> .05). Both work-life and work-life balance qualities were also found to jointly influence the job satisfaction of these bank employees. It was recommended that organizations take straightforward steps to improve the working conditions in which people work and the organizations' physical and psychological working environment that will improve the level of job satisfaction that their employees experience.